Struktur Komunitas Collembola Pada Habitat Gua Lowo dan Kebun Warga di Desa Melirang Kabupaten Gresik, Jawa Timur - Siti Zulaikha; Saiful Bahri; Saiku Rokhim; Ita Ainun Jariyah; Nirmala Fitria Firdhausi; Ria Safitri (Pro-Life, 2022)
Collembola is one of the soil fauna that acts as the smallest constituent component for the balance of the ecosystem. This study aims to compare the structure of the Collembola community in the habitat of Lowo Cave and Citizen's Garden in Melirang Village, Gresik Regency. This research uses descriptive exploratory research with soil drill method for soil sampling and pitfall trap for ground surface insect traps. Based on Collembola data obtained in Lowo Cave, there are 3 species with a total of 87 individuals, while in Citizen's Garden there are 6 Collembola species with a total of 145 individuals The results of the analysis of this study indicate that the Diversity Index value in the Lowo Cave habitat is H'= 0.859735 and in the Citizen's Garden a habitat with the value H' = 1.475675, the Evenness Index value in the Lowo Cave is E = 0.782565 and in the Citizen's Garden with a value of E = 0.82359, the value of the Dominance Index in Gua Lowo is 0.48104 and in the Citizen's Garden is 0.282949, the Relative Frequency of Ascocyrtus sp. and Hypogastrura consanguinea have a relative frequency of 100%.